Important research progress in clinical practice for early breast cancer in 2024 - LI Xing, PENG Ziqi, YU Xinmiao, JIN Feng (Zhongguo aizheng zazhi)
The diagnosis rate of early breast cancer has significantly increased with the proliferation of tumor screening and heightened health awareness. Clinical research, as the evidence base for guidelines and consensus, provides optimized treatment plans for breast cancer. This article summarized and classified several pivotal clinical studies that changed the clinical practice of early breast cancer, according to updates in domestic and international guidelines and consensus from 2023 to 2024. These included the optimization of neoadjuvant and adjuvant therapies, the escalation of adjuvant endocrine therapy, the optimization of local treatment, and attention to quality of life, etc. In the optimization of neoadjuvant and adjuvant therapies, the KEYNOTE-522 study established the therapeutic role of pembrolizumab combined with chemotherapy in early high-risk triple-negative breast cancer (TNBC). The FDChina study confirmed the non-inferiority of the subcutaneous formulation of trastuzumab combined with pertuzumab (H+P) in neoadjuvant treatment of human epidermal growth factor receptor 2 (HER2)-positive breast cancer, offering a more convenient administration method. The KATHERINE study clarified the adjuvant role of trastuzumab emtansine (T-DM1) in HER2-positive breast cancer patients who did not achieve a pathologic complete response (pCR) after neoadjuvant therapy. In the escalation of adjuvant endocrine therapy, the MonarchE and NATALEE studies confirmed the efficacy of abemaciclib and ribociclib combined with endocrine therapy in high-risk hormone receptor (HR)-positive HER2-negative early breast cancer patients, promoting the application of cyclin-dependent kinase (CDK) 4/6 inhibitors in early breast cancer treatment. In the optimization of local treatment, the ACOSOG Z11102 study supported the feasibility of breast-conserving surgery for multicentric breast cancer, the SENOMAC study provided evidence for exempting sentinel lymph node (SLN) low-burden breast cancer patients from axillary lymph node dissection (ALND), the SOUND study supported the exemption of sentinel lymph node biopsy (SLNB) for T1 and cN0 breast cancer patients, and the ICARO study suggested the feasibility of exempting ALND for patients with isolated tumor cells (ITCs) found after neoadjuvant chemotherapy with SLNB or targeted axillary dissection (TAD). The NSABP B-51/RTOG 1304 study provided a basis for the de-escalation of regional lymph node irradiation (RNI) and local treatment in ypN0 breast cancer after neoadjuvant therapy. In terms of quality of life and chemoprevention, the POSITIVE study proposed a protocol for pausing endocrine therapy for breast cancer patients with fertility needs, and the TAM-01 and IBIS-Ⅱ studies provided strong evidence-based medical evidence for chemoprevention in high-risk breast cancer patients. These pivotal clinical studies have profoundly impacted the clinical practice of early-stage breast cancer, not only optimizing treatment plans but also focusing on the quality of life and disease prevention of breast cancer patients. This article discussed the impact of the aforementioned clinical studies on the clinical practice of early breast cancer, centered on updates to various domestic and international breast cancer diagnosis and treatment guidelines and consensus.